On the application of the volume free strain energy density method to blunt V-notches under mixed mode condition. (1st March 2021) - Foti, Pietro; Razavi, Seyed Mohammad Javad; Ayatollahi, Majid Reza; Marsavina, Liviu; Berto, Filippo
Highlights: The volume free SED method is applied to blunt notches under mixed mode conditions. The computational effort to apply the SED method is reduced of at least 50%. The application of the method as a postprocessing tool has been verified. Abstract: This work investigates the possibility to apply the strain energy density method, as regards blunt V-notches under mixed loading condition, through finite element models with a free mesh pattern. It is worth underlining that the conventional procedure for the application of this method to this kind of components requires two different numerical simulations. A first simulation is needed to define the point of maximum of the first principal stress field along the notch fillet whose position represents an input for a second simulation to build the control volume in the right position to apply the method. Several numerical analyses were carried out to compare the conventional procedure of the method with this new procedure that allows the application of the method as a post-processing tool. The main advantage of this new procedure applied to components without stress singularity is that, by accepting an error that depends on the mesh refinement, the efforts of designers and researchers and the calculation time are decreased. The error in evaluating the SED value has been found to have a zero average value with a standard deviation of 1% and a maximum absolute value of 4.5% having a ratio between the main geometrical parameters of the control volume and the average mesh size comprised in the following range 3 < m i n R 0 ; γ / 2 / Size averaged ≤ 5 . Dealing with this kind of components, the calculation time decreases by at least 50% requiring one simulation instead of the two requested by the conventional procedure.